2022
DOI: 10.1021/acs.iecr.2c03424
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Self-Assembly Process during Gelation and Crystallization of Cefradine

Abstract: In recent years, low-molecular-weight assemblies have emerged as remarkable building blocks of supramolecular structures. To fully understand the molecular assembly mechanism of small organic molecules, cefradine was used as a model compound to investigate the supramolecular self-assembly process and its results using microscopy, vibrational and circular dichroism spectroscopies, conformation and dynamics studies, nuclear magnetic resonance, and X-ray crystallography. It was found that cefradine would undergo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Density functional theory (DFT) calculations with dispersion correction (D3) are important advances in the attempt to more accurately estimate the energy of intermolecular interactions with low computational cost . This has been a powerful and widely used tool in developing proposals for nucleation mechanisms at the molecular level …”
Section: Introductionmentioning
confidence: 99%
“…Density functional theory (DFT) calculations with dispersion correction (D3) are important advances in the attempt to more accurately estimate the energy of intermolecular interactions with low computational cost . This has been a powerful and widely used tool in developing proposals for nucleation mechanisms at the molecular level …”
Section: Introductionmentioning
confidence: 99%
“…Molecular hydrogels with amphipathicity based on carbohydrates, peptides, antibiotics, and nucleotides have been reported extensively, such as lanreotide, ganirelix, d -glucosamine, pamidronate, ibuprofen, and acetaminophen . Furthermore, it has been reported that it is possible to convert almost any type of drug molecule into a hydrogel via suitable structural modification/design or minimal synthetic efforts. , However, most self-delivery systems were derived from structurally modified agents (like salt formation) or in organic solvents. And the modified therapeutic agents usually carry the risk of reduced efficacy and accompanying biotoxicity, and organic solvents directly involved in assembly are cytotoxic to some extent. Many challenges still need to be overcome, such as modifying drugs to form hydrogels without compromising their bioresorbability, ensuring good stability of the hydrogel, and achieving self-assembly without inducing undesired promiscuous binding or inhibition …”
Section: Introductionmentioning
confidence: 99%
“…In this work, cefradine (Figure , C 16 H 19 N 3 O 4 S, CAS registry No: 38821-53-3), a first-generation semisynthetic cephalosporin, was used as the model compound for colloidal suspension analysis during crystallization. Generally, cefradine is prepared by reaction crystallization in an aqueous solution by adjusting the pH. With the precipitation of crystals, colloidal suspensions will generally be formed and the fluid would become viscous. To understand the formation mechanism of the colloidal suspension during the crystallization process, multistage and multiscale studies were carried out.…”
Section: Introductionmentioning
confidence: 99%